Indirect search for dark matter in dwarf spheroidal galaxies with Cherenkov Telescope Array - Nakashima, Danielle Kaori (2018)
Dark matter (DM), whose nature and interaction mechanisms are still an open issue, constitutes about 25 % of the Universe energy density. Weakly Interacting Massive Particles (WIMPs) are considered as strong candidates for particle DM and their search is conveniently carried out through the detection of gamma rays. The newly discovered ultra-faint dwarf spheroidal galaxies (dSphs), located in the vicinity of the Galaxy, exhibit high values of the mass to luminosity ratio, and are therefore considered as strongly dominated by DM. These objects are within reach of the Cherenkov Telescope Array (CTA), which is the future project for gamma-ray astronomy, with an better sensitivity (one order of magnitude) with respect to the current generation experiments. The main goal of the present work is the study of the sensitivity of CTA to WIMPs DM particles, by simulating the observation of the ultra-faint dwarf spherical galaxies Triangulum II, Reticulum II and Carina III, as well as of the classical dwarf galaxy Sculptor, for different annihilation channels, between 70 GeV and 100 TeV. The sensitivity curve in the WIMPs parameter space (velocity-averaged annihilation cross section < σ ν > and DM mass mDM) was computed. We found that, within the sample of dwarf galaxies tested, Triangulum II is the most promising source, able to reach the thermal freeze-out values in the annihilation channel τ+τ- for only 50 hours of observation. Our result, the first estimation of the sensitivity for DM searches in ultra-faint dwarfs with CTA, is consistent with results from current generation experiments, showing better performance over an extended energy range. The limited sample of available stars in the targets induces uncertainties on the DM content. Future measurements, leading to a better understanding of the sources dynamic equilibrium, can improve this situation. Even so, the combination of the high DM content in the ultra-faint dwarf galaxies, together with the excellent expected performance of the future CTA, provides a promising result for indirect DM searches.